Xyloglucan based mucosal nanovaccine for immunological protection against brucellosis developed by supercritical fluid technology - Swati Vyas; Sagar Dhoble; Vinod Ghodake; V. Patravale (Elsevier, 2020)
Vaccines delivered via the mucosal route have logistic benefits over parenteral or intramuscular vaccines as they offer patient compliance. This study presents the first intranasal, controlled release, subunit nanovaccine comprising mucoadhesive tamarind seed polymer (xyloglucan) based nanoparticles produced using an efficient, environmentally compatible, and industrially scalable technique: rapid expansion of supercritical solution. The nanovaccine formulation aimed against brucellosis comprised xyloglucan nanoparticles loaded separately with antigenic acellular lipopolysaccharides from B. abortus (S19) and the immunoadjuvant quillaja saponin. The nanovaccine elicited prolonged humoral and cell-mediated immunity in female Balb/c mice. Nasal vaccination with the nanovaccine resulted in higher levels of mucosal IgA and IgG than with an aqueous solution of soluble lipopolysaccharides and quillaja saponin. Systemic immunity triggered by the nanovaccine was evidenced by higher IgG levels in sera post priming and boosting. The nanovaccine induced a mixed Th1/Th2 type of immunity with higher IgG2a levels and thus a polarized Th1 response. The results suggest that the nanovaccine administered by homologous nasal route can prime the immune system via the mucosal and systemic pathways and is a good candidate for vaccine delivery.